Co-Design of Magnet-Edge One Step Slotting and Stator Dummy Slots to Reduce Cogging Torque and Unbalanced Magnetic Pull - Gita Wardhana; Tajuddin Nur; Lucio Alfredo Correia; Herlina Herlina; Maria Angela Kartawijaya (Fakultas Teknik Universitas Pancasila, 2026)
Low-speed wind generators require low cogging torque to ensure reliable start-up and low unbalanced magnetic pull to reduce vibration and bearing stress. This study examines a co-design approach that combines one-step magnet-edge slotting and stator dummy slots in a 24-slot/20-pole fractional-slot permanent magnet machine. Three configurations were analysed using two-dimensional finite element analysis in FEMM 4.2: the baseline model, the one-step magnet-edge slotting model, and the integrated one-step magnet-edge slotting + dummy-slot model. Cogging torque was calculated from Maxwell stress in the air gap, while unbalanced magnetic pull was evaluated through horizontal and vertical electromagnetic force components. The results show that one-step magnet-edge slotting reduces peak cogging torque by about 74.3% compared with the baseline model. The combined one-step magnet-edge slotting + dummy-slot design achieves a larger reduction of about 99.4%. This configuration also decreases unbalanced magnetic pull by approximately 92% on the X-axis and 90% on the Y-axis. When the unbalanced magnetic pull effect is included, the effective cogging-torque reduction remains about 98.9%. These findings indicate that integrating rotor-side magnet-edge slotting with stator-side permeance shaping provides an effective passive strategy for improving start-up performance and radial-force balance in low-speed permanent magnet wind generators .